A Comparative Analysis of Medical Malpractice Law in Indonesia: Evaluating the Shift from Law No. 36 of 2009 to Law No. 17 of 2023 - Friska Friska; Riki Zulfiko (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Health law is a critical branch of law governing legal relations in the health sector. Medical malpractice, arising from professional negligence that causes patient harm or death, reflects failures in healthcare delivery. Rising malpractice cases indicate public dissatisfaction and serious legal ethical challenges. Objective: This study analyzes regulatory changes on medical malpractice under Indonesia’s Health Law No. 17 of 2023 compared with Law No. 36 of 2009, focusing on shifts in legal protection between medical personnel and patients. Methods: This normative juridical research applies a statutory approach. Analysis compares key provisions on malpractice, dispute resolution, and sanctions in both laws. Data derive from primary legal materials and secondary sources, analyzed qualitatively. Results: Law No. 17/2023 introduces major changes: mandatory ethics council recommendations prior to investigation, compulsory restorative justice mechanisms, and reduced criminal sanctions for negligence causing disability or death. These provisions strengthen protection for medical personnel but create procedural barriers for patients seeking remedies, potentially weakening patient rights. Conclusion: Indonesia’s malpractice regime now favors medical professionals. Although intended to limit defensive medicine, the shift risks marginalizing patients and therefore requires stronger non-litigious patient protection mechanisms and a credible, independent ethics council to sustain justice and public trust.